Arsenic trioxide-induced acute kidney injury: OPA1- and Drp1-mediated mitochondrial dynamics imbalance, PINK1/Parkin-dependent mitophagy, and Chuanhuang Fang III - Wang, Peiji; Wu, Zicong; Song, Zhiyong; Deng, Xingyu; Zhang, Yifan; Gong, Xuezhong (Frontiers in Molecular Biosciences, 2026)
PurposeAcute kidney injury (AKI) remains a global health concern with limited therapies. Among its causes, arsenic (AS)-induced AKI (AI-AKI), exemplified by the antitumor agent arsenic trioxide (ATO), represents an emerging clinical challenge. Despite its clinical efficacy in treating AI-AKI, the protective mechanism of Chuanhuang Fang III (CHF) remains unclear. This study aimed to investigate the mechanisms and therapeutic targets of CHF against AI-AKI.MethodsClassic AI-AKI rat model was established, and subsequently treated with graded doses of CHF. CHF constituents were identified. Renal pathology, renal function, and AKI biomarkers were detected. Mitochondrial quality control-related parameters were detected as follows: 1) transmission electron microscopy was employed to assess mitophagy; 2) Western blotting was performed to evaluate mitochondrial dynamics- and mitophagy-related proteins, while differential gene expression and pathway enrichment were analyzed by RNA-sequencing; 3) mitochondrial membrane potential and mitochondrial ROS levels were measured in freshly isolated renal cortical mitochondria by JC-1 staining and flow cytometry. The HK-2 cell line was used to further elucidate the underlying mechanisms of AI-AKI, and the effect of antioxidant NAC was observed simultaneously.ResultsATO exposure resulted in increased serum creatinine, mitochondrial dysfunction, elevated mitochondrial ROS levels, and promoted apoptosis, autophagy, and mitophagy in renal tubular epithelial cells. It also downregulated the mitochondrial fusion protein OPA1 and upregulated the fission protein Drp1. These effects correlated with the activation of the PINK1/Parkin mitophagy pathway, as well as increased expression of BNIP3, NIX, LC3B and Bax, and decreased anti-apoptotic protein Bcl-2. Transcriptomic analysis indicated that the key signaling pathways in AI-AKI were associated with mitophagy, autophagy, mitochondrial function and apoptosis. CHF attenuated AI-AKI by regulating OPA1/Drp1 balance and PINK1/Parkin-mediated mitophagy and counteracted the associated pathological processes. In vitro experiments using the HK-2 cell line provided further evidence supporting the in vivo findings.ConclusionThe pathogenesis of clinical-dose ATO-induced AKI involves OPA1- and Drp1-mediated mitochondrial dynamics imbalance and PINK1/Parkin-dependent mitophagy in renal tubular epithelial cells, CHF ameliorated this injury by restoring mitochondrial quality control, highlighting its therapeutic potential against AI-AKI.